Tuberculosis course in a patient with Fahr’s disease (a clinical case report) - Raznatovska, O. M.; Fedorets, A. V.; Sikorska, M. V.; Noreiko, S. B. (Zaporozhye Medical Journal, 2018)
In the present context, pulmonary tuberculosis, especially its resistant forms, is an urgent problem of society, not only inUkraine, but also throughout the world. As is known, comorbidities make difficult not only tuberculosis diagnostics, but also its treatment. Tuberculosis can either develop on the background of any diseases or cause their development and exacerbations. On account of this there are rare diseases of various organs and systems which are characterized by a long absence of clinical symptoms. Work objective is to draw the attention of doctors to the combined course of tuberculosis and rare neurological diseases such as Fahr’s disease. Materials and methods. The article deals with the clinical case based on own observations of the pulmonary multidrug-resistant tuberculosis (MRTB) development in a patient with Fahr’s disease diagnosed in the process of tuberculosis treatment. The patient received inpatient treatment in the Department of Pulmonary Tuberculosis No. 3 of the clinical base of the Phthisiology and Pulmonology Department of the ZSMU in the Communal Institution “Zaporizhzhia Regional Tuberculosis Clinical Dispensary”. Results of own observations. It has been defined that the patient had experienced slow asymptomatic course of Fahr’s disease prior to the onset of pulmonary MRTB. Probably, the toxic effect of antimycobacterial drugs provoked clinical manifestations of Fahr’s disease in the form of neurological symptoms. If Fahr’s disease had been timely diagnosed, antimicrobial therapy would have been prescribed with appropriate initial treatment correction through the exclusion of antimycobacterial drugs with neurotoxic effects from the chemotherapy regimen. Such an approach might not have exacerbated the underlying disease. Conclusions. In a patient with Fahr’s disease the pulmonary MRTB can be treated provided constant monitoring by a neuropathologist with the prescription of adequate symptomatic and pathogenetic therapy that could prevent severe neurological disorders development.